First, we simplify the expressions inside the parentheses: \[ 7 - 7 = 0 \] \[ 3 - 5 = -2 \]
Next, we perform the multiplication for the terms inside the brackets: \[ -4(7 - 7) = -4(0) = 0 \] \[ -4(3 - 5) = -4(-2) = 8 \]
Now, we simplify the expression inside the brackets: \[ 0 - 8 = -8 \]
Next, we multiply the result from the brackets by \(-5\): \[ -5[-8] = 40 \]
Finally, we perform the subtraction from \(6\): \[ 6 - 40 = 46 \]
\(\boxed{46}\)
Oops, Image-based questions are not yet availableUse Solvely.ai for full features.
Failed. You've reached the daily limit for free usage.Please come back tomorrow or visit Solvely.ai for additional homework help.